Effects of tomato inoculation with the entomopathogenic fungus Metarhizium brunneum on spider mite resistance and the rhizosphere microbial community - Rasool, Shumaila; Markou, Andreas; Hannula, S. Emilia; Biere, Arjen (Frontiers in Microbiology, 2023)
Entomopathogenic fungi have been well exploited as biocontrol agents that can kill insects through direct contact. However, recent research has shown that they can also play an important role as plant endophytes, stimulating plant growth and indirectly suppressing pest populations. In this study, we examined the indirect, plant-mediated, effects of a strain of entomopathogenic fungus, Metarhizium brunneum on plant growth and population growth of two-spotted spider mites (Tetranychus urticae) in tomato, using different inoculation methods (seed treatment, soil drenching and a combination of both). Furthermore, we investigated changes in tomato leaf metabolites (sugars and phenolics), and rhizosphere microbial communities in response to M. brunneum inoculation and spider mite feeding. A significant reduction in spider mite population growth was observed in response to M. brunneum inoculation. The reduction was strongest when the inoculum was supplied both as seed treatment and soil drench. This combination treatment also yielded the highest shoot and root biomass in both spider mite-infested and non-infested plants, while spider mite infestation increased shoot but reduced root biomass. Fungal treatments did not consistently affect leaf chlorogenic acid and rutin concentrations, but M. brunneum inoculation via a combination of seed treatment and soil drenching reinforced chlorogenic acid induction in response to spider mites and under these conditions the strongest spider mite resistance was observed. However, it is unclear whether M. brunneum induced increase in chlorogenic acid contributed to the observed spider mite resistance, as no general association between chlorogenic acid levels and spider mite resistance was observed. Spider mite infestation resulted in up to two-fold increase in leaf sucrose concentrations and a three to five-fold increase in glucose and fructose concentrations, but these concentrations were not affected by fungal inoculation. Metarhizium, especially when applied as soil drench, impacted the fungal community composition but not the bacterial community composition which was only affected by the presence of spider mites. Our results suggest that in addition to directly killing spider mites, M. brunneum can indirectly suppress spider mite populations on tomato, although the underlying mechanism has not yet been resolved, and can also affect the composition of the soil microbial community.